Optimized recovery of DNA and subsequent short tandem repeat profiling of different tissues sampled from embalmed human cadavers - Kofi Adjapong Afrifah; Alexander Badu-Boateng; Samuel Antwi-Akomeah; Osei Owusu-Afriyie; Mishael Yankey (Journal of Forensic Science and Medicine, 2023)
Introduction: Storage of specimens sampled from human remains for pathological testing, embalming for burial purposes, and for human identification often requires formalin fixation and/or paraffin embedding. Current knowledge in molecular biology techniques and forensic DNA analysis makes it possible to optimize the extraction of amplifiable DNA from formalin-fixed tissues by improving the pre-treatment, optimizing the digestion condition of proteinase K, simplifying the extraction protocol and purifying the extracted DNA with optimized volumes of alcohol. Aim: This research sought to extract amplifiable DNA from thirteen brain, bone marrow and cartilage samples from four formalin embalmed human cadavers. Materials and Methods: Brain, cartilage and bone marrow samples were taken from four different cadavers at autopsy at the Ghana Police Hospital mortuary in Accra, Ghana sixty-two days after embalming. An optimized preparation and DNA extraction protocol was carried out on all the samples. Brain samples were also taken from a non-formalin treated fifth cadaver of known STR profile, and standard DNA extraction performed to serve as positive control. Results: Our optimized protocol yielded detectable quantities of DNA from the samples when quantified with the 7500 Real-Time PCR equipment. The extracted DNA also yielded full STR profiles with varying peak heights for forensic identification purposes. The measured degradation indexes of the DNA samples were greater than 1.0, with peak heights of generated STR profiles above the limits of detection of the 3500 genetic analyzer. Conclusion: Our current study demonstrated an optimized method of DNA extraction from tissues (brain, cartilage and bone marrow) sampled from formalin embalmed human cadavers. The optimized protocol reduced the concentration of formalin fixation residues in extracted DNA from formalin-fixed tissues, thereby improving the amplification efficiency for STR profiling. Brain, bone marrow and cartilages can be a good source of DNA from embalmed and degraded human remains, though for skeletonized human remains together with teeth and long bones.